ТЕХНОЛОГІЯ АНАЛІЗУ ПЕРСОНАЛУ ПРОМИСЛОВИХ ПІДПРИЄМСТВ НА ОСНОВІ КЛАСТЕРИЗАЦІЇ - Grynyova, V.M.; Mazhnyk, L.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The article describes main blocks of the cluster-based technology for analysis of industrial enterprise’s personnel, gives grounds for choosing the cluster analysis and defines the number of groups for enterprises’ classification by the most important personnel characteristics.